Scaling Approach to Determine Superconducting Anisotropy - Yadav, Anil Kumar (New Approaches in Engineering Research Vol. 10, 2021)
Anisotropy is the crystal property that effects may be observed in various direction dependent physical properties. It plays an import role in high temperature superconductors too. Layered high temperature superconductor’s exhibits highest superconducting anisotropy. Conventional approach is one of the ways to determine superconducting anisotropy; however, the estimation process of anisotropy in this includes some approximation errors. Scaling approach is the alternate way to measure the anisotropy that provides more accurate results comparatively. Both methods are described here and applied to find the superconducting anisotropy of FeSe0.5Te0.5 single crystal, which is an iron based superconductor.